Enhancing agricultural output: investigating the impact of advanced organic formulations on crop productivity, nutrient use efficiency, and profitability in a multi-crop system - Garg, Kamal; Dhar, Shiva; Kumar, Sanjeev; Azman, Elisa Azura; Sharma, V.K.; Meena, Rajendra Prasad; Hashim, Mohammad; Awasthi, Mukesh Kumar; Kumar, Sourabh; Onte, Santosh; Kumar, Dileep; Giri, Balendu Shekher; et al. (Academic Press, 2024)
The significance of integrating agricultural by-products such as paddy husk ash (PHA) and potato peels with organic fertilizers lies in enhancing soil fertility, increasing crop yields, and reducing reliance on traditional organic fertilizers like farmyard manure (FYM) or compost alone. Grounded in sustainable agriculture and nutrient management frameworks, this study examines the impact of diverse formulations derived from agricultural waste on productivity, nutrient efficiency, and profitability in a pigeon pea–vegetable mustard–okra cropping system. A two-year field experiment (2020–2022) at ICAR-IARI, New Delhi tested seven nutrient sources viz., (T1) control, (T2) 100% RDN through FYM, (T3) 100% RDN through improved RRC, (T4) 100% RDN through PHA based formulation, (T5) 75% RDN through PHA based formulation, (T6) 100% RDN through PPC based formulation and (T7) 75% RDN through PPC based formulation that were tested in RBD and replicated thrice. Treatment T4 had significant effect on seed yield of pigeon pea (1.89 ± 0.09 and 1.97 ± 0.12 t ha−1), leaf yield of vegetable mustard (81.57 ± 4.59 and 82.97 ± 4.17 t ha−1), and fruit yield of okra (13.54 ± 0.82 and 13.78 ± 0.81 t ha−1) grown in rotation, followed by treatment T6 and T2 during both the years respectively over control. Enhanced system uptake of N, P and K along with system gross and net returns in T4, showed increases of 78.9%, 83.8%, 72.4%, 54.4% and 56.8% in the first year and 77.5%, 80.8%, 77.7%, 54.8% and 57.4% in the second year, respectively, over control. Treatment T4 significantly improved apparent recovery by 66.3% and 69.2% in pigeon pea, 64.7% and 47.9% in vegetable mustard, and 72.7% and 79.4% in okra over T3, averaged across two years. Based on the above findings, (T4) 100% RDN through PHA-based formulation, and (T6) 100% RDN through PPC-based formulation can be recommended for areas with a shortage of FYM but availability of rice husk ash/potato peels for sustainable agricultural wastes and improved sustainability.